Activating Mutation of SHP2 Establishes a Tumorigenic Phonotype Through Cell-Autonomous and Non-Cell-Autonomous Mechanisms - Dong, Lei; Han, Da; Meng, Xinyi; Xu, Mengchuan; Zheng, Chuwen; Xia, Qin (Frontiers in Cell and Developmental Biology, 2021)
Gain-of-function mutation of SHP2 is a central regulator in tumorigenesis and cancer progression through cell-autonomous mechanisms. Activating mutation of SHP2 in microenvironment was identified to promote cancerous transformation of hematopoietic stem cell in non-autonomous mechanisms. It is interesting to see whether therapies directed against SHP2 in tumor or microenvironmental cells augment anti-tumor efficacy. In this review, we summarized different types of gain-of-function SHP2 mutations from human disease. In general, gain-of-function mutations destroy the auto-inhibition state from wild-type SHP2, leading to consistency activation of SHP2. We illustrated how somatic or germline mutation of SHP2 plays oncogenic role in tumorigenesis, stemness maintenance, invasion, etc. Moreover, the small molecule SHP2 inhibitors are considered as potential strategy for enhancing the efficacy of anti-tumor immunotherapy and chemotherapy. We also discussed the interconnection between phase separation and activating mutation of SHP2 in drug resistance of anti-tumor therapy.